(3OjhGf GdTjN QeVGf Hf ehSi GdZWjais - (3QeVGf Hf ehSi Hf eMehO Hf CMeO, GHf YWja GdOeTbj GdoYnWrjaj,J (B1095 (3g` s
(3ChdgG (B:s
(3GdMeO ddg deG cGf GdTYQ eYjGQ GdYbd h hYfhGf GdEfSGf hJQLeGf GdHjGf s
(3BNQgG (B:s
(3habg Gddg JYGdi ddSOGO s
(3HgG fXGe GdJYbjHIs
(3Ydi dhMI GdYfhGf Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B172s
Keywords: (3GdCOHs